TRAINING APPLICATION OF FIELD TRIP LEARNING METHODS FOR TEACHERS OF HISTORY IN KUPANG CITY - Malkisedek Taneo ,; Fransina Aprilyse Ndoen ,; Madu, Aleksius (IJRDO- Journal of Educational Research, 2019)
The aim of the science and technology activities for this community is to help history teachers in Kupang City carry out classroom learning, write articles and scientific journals. While the background of the holding of this IbM is because the ability of history teachers in Kupang City to apply the learning methods especially the field trip learning method in general is still not maximal, but in reality the application of learning methods in class is one of the main supporting factors for the success of the learning implementation is to measure the level of student success in learning. The specific target to be achieved through science and technology activities for the community is to increase the ability of teachers to apply field trip learning methods and other learning methods in class correctly and appropriately.The method used in this activity is planning, action, observation and evaluation and reflection. Provision of material related to the field trip learning method, the preparation of learning tools based on the steps of the field trip learning method then participants are given the opportunity to discuss to compile the learning tools, as well as how to simulate the field trip learning method in class and outside the classroom.The results achieved in this dedication activity can be concluded 1) teachers with historical educational background can be guided in the preparation of learning tools based on the field trip learning model, and implement them in class 2) quantitatively, these activities have not produced satisfactory results, but in Qualitative teachers are helped by the learning simulation conducted by the community service team and later can be used as a learning model to be applied in their schools.